Comparative Study of the Retrogradation of Intermediate Water Content Waxy Maize, Wheat, and Potato Starches - Ottenhof, M.A.; Hill, S.E.; Farhat, I.A.
The retrogradation of extruded starches from three different botanical sources was studied in concentrated conditions (34 ( 1
Keywords: STARCH RETROGRADATION; AMYLOPECTIN; ISOTHERMAL CALORIMETRY; MOLECULAR ORDER; STAL